Progression in the Morphology of Fuel Cell Membranes upon Conjoint Chemical and Mechanical Degradation. Issue 7 (16th April 2016) - Venkatesan, Senthil velan; Lim, Chan; Holdcroft, Steven; Kjeang, Erik
Abstract : Ionomer membranes used to separate the electrodes in polymer electrolyte fuel cells are known to degrade both chemically and mechanically during regular fuel cell operation and may ultimately result in lifetime-limiting failure. The objective of the present work is to understand the effects of combined chemical and mechanical stresses on the mesoscale morphology of the membrane and its role in the overall degradation process. The mesoscale effects of sulfonic acid group loss and fluoride release on the phase segregated morphology of the membrane are analyzed using contrast-enhanced transmission electron microscopy and energy dispersive X-ray spectroscopy. The end-of-life ionic domain size of the ionomer is shown to be substantially enlarged compared to the pristine membrane state. Elemental mapping overlayed with the binary ionic and non-ionic morphology reveals mesoscopic void regions in the degraded material that are depleted of ionomer fluorine and carbon and considered susceptible to micro-crack initiation. A larger, severely degraded void region is also identified which contains evidence of hygrothermal stress induced localized ionomer crazing as a potential nucleation site for macroscopic fracture development. The synergetic effects of chemical and mechanical degradation on the progressive changes in the observed mesoscale morphology are discussed.